Do Sports-related Concussions Induce Subsequent Injuries in Elite Male Football Players? - Beaudouin, Florian; Tröss, Tobias; Hadji, Abed; Steendahl, Ida Bo; Meyer, Tim; Fünten, Karen Aus der (International Journal of Sports Medicine, 2023)
To assess the players’ risk of a subsequent injury after sustaining concussive injuries and their return-to-competition in German professional men’s football. A prospective injury database in the 1st Bundesliga was created encompassing 7 seasons (2014/15–2020/21). Cox proportional hazard model analyzed whether a concussive injury increased the risk of a subsequent injury in the first year after the index injury. 6,651 injuries were reported (n=182 concussive injuries). The incidence rate was 0.15 (95% CI 0.13–0.17) per 1000 football hours. A concussive injury was associated with only a slightly numerical higher risk of 7% (HR=1.07, 95% CI 0.78–1.47) in the subsequent year after the injury compared to a randomly selected non-concussive injury, but the effect was not significant. The risk was higher after 6–12 months post-SRC reaching 70% (HR=1.70, 95% CI 1.15–2.52). For 0–3 months (HR=0.76, 95% CI 0.48–1.20) and 3–6 months (HR=0.97, 95% CI 0.62–1.50) the injury risk was lower. The present data do not confirm previously published investigations about an increased injury risk after SRC. Contrasting effects of lower hazard ratios were found early after SRC, followed by an increase after 6–12 months. Further research should look into compliance rates with regards to return-to-competition protocols.
Keywords: head injury; traumatic brain injury; soccer; prevention; sequalae